Erratum: Genetic loci associated with heart rate variability and their effects on cardiac disease risk - Ilja M. Nolte (Nature Portfolio, 2017)
Nature Communications 8: Article number: 15805 (2017); Published: 14 June 2017; Updated: 2 August 2017 In Supplementary Fig. 10 of this Article, images for panels a and b were inadvertently omitted. The correct version of Supplementary Fig. 10 is provided as Supplementary Information associated withthis Erratum.